Checklist of Cyanobacteria from the State of Pará (Brazil) - Nunes, Daniela Santana (2023)
Regarding the families, 27 families were recorded, among which the families with the highest representativeness were: Merismopediaceae (22 taxa), Oscillatoriaceae (17 taxa), Microcystaceae and Microcoleaceae (both with 13 taxa each). Among the Cyanobacteria taxa compiled from the literature (60 taxa), 63.33% occurred exclusively in continental waters; 8.33% were recorded exclusively in estuaries; and 28.33% occurred both in continental waters and in estuaries. Among the taxa referenced in the herbaria collections, only 1 species is considered exclusively marine-estuarine, the others, all of which come from samples of continental waters.